Gestão estratégica e o plano de desenvolvimento da escola na rede escolar do município de Itaquaquecetuba, SP - Barbosa, Verônica Cosmo (2015)
Based on contemporary educational management, this research targeted on the concepts of strategic management in educational institutions, democratic participatory management, and the use of management tools to support the work of the management of public schools of basic education. In this context, the Development Plan of the School (PDE-School) is presented by the Ministry of Education (MEC), as an administrative tool whose goal is to improve the administrative and academic performance of schools and the IDEB observed in the period from 2005 to 2013 pointed out problems in academic performance in schools, since the basic education schools in the municipality studied have not reached the average projected. Thus, the research turns to the PDE-School, featuring the difficulties to use the program as a strategic management tool in basic education schools in the municipality of Itaquaquecetuba, SP. To perform this, we used quantitative research, statistical and exploratory, through a questionnaire closed to the management team of sixty-three (63) basic education schools in the city using the PDE-School. The results have enhanced some difficulties in using the tool, however, indicate that it is possible to use it. The research also suggests a pedagogical approach that uses performance indicators to address the educational problems and plan actions, given this, relevant in the context of strategic management and administrative and pedagogic efficiency of the school as it is understood the importance of school staff actively participating in the educational process of the school.